Determination of acute appendicitis histologic subtypes by MDCT findings (Annals of Medical Research, 2021)
Aim: Our aim was to investigate if histological subtypes of acute appendicitis (AA) can be predicted by multidetector computed tomography (MDCT) and laboratory findings.Material and Methods: A retrospective search of the hospital database to identify patients who underwent appendectomy and had an abdominal MDCT scan and laboratory tests including white blood cell (WBC) count and c-reactive protein (CRP) available before the operation revealed 123 patients (mean age: 25.69 ± 17.23 years). Histopathological results were classified as mucosal, gangrenous and suppurative AA. MDCT scans of the patients were evaluated for appendix diameter, appendix wall thickness, presence of pericecal fluid and extraluminal air. The relationship between MDCT and laboratory findings and histological subtypes of AA were assessed.Results: There were 24 (19.5%) mucosal, 47 (38.2%) suppurative and 52 (42.3%) gangrenous AA. WBC count, CRP level, appendix wall thickness and appendix diameter was significantly different between mucosal and gangrenous AA (p 0.05) and between suppurative and gangrenous AA (p 0.05). However, there was no significant difference between mucosal and suppurative AA in terms of all variables (p = 0.752, 0.551, 0.756, 0.250 and 0.051, respectively). Presence of pericecal fluid was 92.2% sensitive and 93.1% specific for gangrenous AA. Presence of extraluminal air was 94.7% sensitive and 97.3% specific for gangrenous AA.Conclusion: AA histologic subtypes can be predicted by especially MDCT findings.